Optimal Day-Ahead Scheduling in AC/DC Hybrid Distribution Networks based on SOCP - Sun, Wei; Zhang, Wen; Zhang, Tingting; Du, Yaxin (2019 IEEE PES Asia-Pacific Power and Energy Engineering Conference (APPEEC), 2019)
DC distribution systems, which can improve the accommodation of renewable energy sources and DC loads, have developed rapidly, leading to the appearance of hybrid AC/DC distribution systems. This paper proposes an optimal day-ahead scheduling model to increase the economy of the system operation considering the high penetration and uncertainty of the distributed generations. The proposed model aims to minimize the active power loss and electricity purchasing cost by coordinating active or reactive power outputs of voltage source converter (VSC), energy storage system (ESS) and static var compensation (SVC), as well as the voltage regulation capability of OLTC. Besides, the load model has been carefully analysed to implement conservation voltage reduction (CVR). In addition, VSC is detailed modelled to capture the coupling between active power and reactive power. Moreover, the second-order cone programming (SOCP) is used in this paper to transform the mixed integer nonlinear programming problem to a convex optimization one, which shortens the solving time. The IEEE 33-bus test system is employed to demonstrate the effectiveness and efficiency of the proposed method.